Germline Mutations in HOXB13 and Prostate-Cancer Risk - Ewing, Charles M; Ray, Anna M; Lange, Ethan M; Zuhlke, Kimberly A; Robbins, Christiane M; Tembe, Waibhav D; Wiley, Kathleen E; Isaacs, Sarah D; Isaacs, William B; Johng, Dorhyun; Wang, Yunfei; Bizon, Chris; et al. (The New England journal of medicine, 2012)
Prostate cancer runs in families. However, the genes that affect the incidence remain largely undefined. The authors have identified a rare germline variant of a homeobox gene, HOXB13, in four families with a history of prostate cancer. Prostate cancer is the most common noncutaneous cancer diagnosed in men in the United States, with more than 240,000 new cases expected in 2011. 1 Despite the demonstration of a strong familial component, identification of the genetic basis for hereditary prostate cancer has been challenging. Linkage studies of families with hereditary prostate cancer have provided inconsistent results. 2 In contrast, genomewide association studies have led to the identification of more than 30 single-nucleotide polymorphisms (SNPs) that are consistently associated with prostate cancer. 3 However, the magnitude of risk elevation attributed to each individual SNP is low, with an increased elevation in risk by . . .